2018
DOI: 10.1017/s0020589317000422
|View full text |Cite
|
Sign up to set email alerts
|

Labour Provisions in Eu and Us Mega-Regional Trade Agreements: Rhetoric and Reality

Abstract: The EU and the US have long called for the linking of trade and labour standards in trade agreements at both the multilateral and bilateral level. This article examines their practice of including labour provisions in trade agreements, with a particular focus on recent attempts to include such provisions on so-called ‘mega-regionals’, which were presented by their proponents as providing the benchmark for labour protection in future trade agreements. It discusses the rationale behind the inclusion of such prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Hamilton (2014) considered the Trans-Pacific Partnership (TPP) and the Transatlantic Trade and Investment Partnership (TTIP) as a response to the stagnation of the Doha Development Round and the rising number of bilateral RTAs. Two afore-mentioned M-RTAs were also studied by Araujo (2018), who stressed the importance of labor market provisions and related limitations in the field of their execution in practice. Kikuchi et al (2018) identified gains for Vietnam resulting from membership in M-RTAs such as RCEP, Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), and the European Union (EU) -Vietnam FTA in respect of productivity growth, capital accumulation, and labor supply changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hamilton (2014) considered the Trans-Pacific Partnership (TPP) and the Transatlantic Trade and Investment Partnership (TTIP) as a response to the stagnation of the Doha Development Round and the rising number of bilateral RTAs. Two afore-mentioned M-RTAs were also studied by Araujo (2018), who stressed the importance of labor market provisions and related limitations in the field of their execution in practice. Kikuchi et al (2018) identified gains for Vietnam resulting from membership in M-RTAs such as RCEP, Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), and the European Union (EU) -Vietnam FTA in respect of productivity growth, capital accumulation, and labor supply changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Criticism was also raised against "soft" regulatory standards developed by international and intergovernmental organizations, such as the ILO's core labor standards or the Organization for Economic Co-operation and Development (OECD) Guidelines for Multinational Enterprises (e.g., Alston, 2004). Even proposals for promoting labor standards through the WTO and international trade agreements (Barry and Reddy 2008) met with skepticism and limited evidence for success in reforming labor conditions in developing countries (Agusti-Panareda et al 2015;Melo Araujo, 2018). Given the persisting "governance gap" in the regulation of global labor, a broad recognition emerged among scholars concerning the need to combine both public and private regulations, on both national and transnational levels, to address the challenge of labor standards in the global economy (Compa, 2008;Distelhorst et al, 2015;Kolben, 2015;Ruggie, 2014).…”
Section: Rethinking Responsibility For Global Labor Standardsmentioning
confidence: 99%